1) 9 – 7y = 25 – 3y;


2) – 2n = 5,6n;


3) 2( 11 – 4a) = 3 – ( 5a + 2);


4) 3( - 5 + c) – 2( c – 4) = 2 – 7( c – 1);


6) 1,2d- 0,5 ( 4d – 1) = -0,7( d – 2);


7) 2,4b – 1,5 = 0,2 – 0,6( 3 – 4b);

1

Ответы и объяснения

2014-02-02T09:09:40+00:00
1) 9 – 7y = 25 – 3y;
-4у=16
у=-4

2) – 2n = 5,6n;
n,6

3) 2( 11 – 4a) = 3 – ( 5a + 2);
22-8а=3-5а-2
21=3а
а=7

4) 3( - 5 + c) – 2( c – 4) = 2 – 7( c – 1);
-15+3с-2с+8=2-7с+7
-7+с=-7с+9
8с=16
с=2



6) 1,2d- 0,5 ( 4d – 1) = -0,7( d – 2);
1,2d-2d+0,5=-0,7d+1,4
-0,1d=0,9
d=-9


7) 2,4b – 1,5 = 0,2 – 0,6( 3 – 4b);
2,4b -1,5=0,2-1,8+2,4b

-0,1